The Effect of Media Variation in Simple Filtration Systems on the Physical Quality of Clean Water Post-Flooding - Nelson Tanjung; David Ramadi (CV. Get Press Indonesia, 2026)
Flooding is one of the most common disasters in Indonesia and often causes deterioration in clean water quality, particularly through increased turbidity, color, and suspended solids. One alternative for improving post-flood water quality is the use of simple filtration systems with different filter media combinations. This study aimed to analyze the effect of filtration media variations on the physical quality of post-flood water. An experimental study using a Completely Randomized Design (CRD) was conducted with four treatments and three replications. Water samples were collected from flood-affected areas in Padang City, West Sumatra, Indonesia. The treatments consisted of P0 (control), P1 (sand and gravel), P2 (sand, gravel, and activated carbon), and P3 (sand, gravel, activated carbon, and zeolite). The observed parameters included turbidity, color, and Total Suspended Solids (TSS). Data were analyzed using One-Way Analysis of Variance (ANOVA) at a 95% confidence level. The results showed that variations in filtration media significantly affected turbidity, color, and TSS (p < 0.05). Descriptively, treatment P3 showed the lowest mean values of turbidity (7.8 NTU), color (11.7 TCU), and TSS (12.0 mg/L) among all treatments. However, because no post hoc analysis was performed, these findings should not be interpreted as evidence that P3 was statistically superior to the other treatment combinations. The values obtained in P3 met the applicable water quality standards for all observed physical parameters. It can be concluded that variations in filtration media significantly influence the physical quality of post-flood water, and a filtration system combining sand, gravel, activated carbon, and zeolite has potential as an appropriate technology for post-disaster clean water provision.